11+ Dance: A Neuromuscular Injury Prevention Exercise Program for Dancers. Issue 5 (10th October 2022) - Kolokythas, Nico; Metsios, George S.; Galloway, Shaun M.; Allen, Nick; Wyon, Matthew A.
ABSTRACT: Epidemiological studies over the past decade indicate high injury prevalence in preprofessional ballet (76%) and professional contemporary and ballet dancers (60–69%). Injuries can have detrimental effects both for the dancers and the dance company. Most injuries are in the lower limb and reported as the gradual onset of overuse. Professional dance companies have reduced injury incidence and severity through the implementation of comprehensive injury audit programs and proactive exercise prescription. Injury prevention research in dance is scarce, and there has been no intervention targeting dance injuries. This article describes the development of 11+ Dance, an injury prevention training program designed for dancers, based on current evidence and best practice on injury prevention in sports. It is a 25–30-minute neuromuscular-based training program focused on strength, balance, and jumping/landing technique, with special attention to ankle, knee, and hip alignment. The high prevalence of injuries reported in the different styles of dance suggests that implementation of an injury prevention program is both the plausible and ethical action to take for all levels of performance.